RANCANG BANGUN TONGKAT PINTAR TUNANETRA BERBASIS MIKROKONTROLER - Parito Parito; I Gusti Agung Komang Diafari Djuni; Nyoman Gunantara (Program Studi Teknik Elektro UNUD, 2021)
Blind part of a community that has limited mobility to the environment in social life. Themobility expected by the visually impaired is not only seen from the social side. We both knowthat the sense of sight is one of the sources of vital information for humans. Most of theinformation obtained by humans comes from the sense of sight. The design of this tool will helpusers avoid objects that are in front, will detect water in the reach of the stick with soundnotifications according to sensor readings. In addition, users also get pick-up mobility ifsomething happens on the road by pressing the emergency button on the device, then thedevice will send a telegram message to the family in the form of the coordinates of the GPSstick location. So that the user of this stick will be easy to find if you need emergency help whenyou are away from home. From the results of testing the tool as a whole, the Blind Smart Stickcan work well, namely it can detect obstacles, and the water in front of it, can issue a warningsound to the user, and can send Telegram messages.